The Terrible Two get worse - Barnett, Mac 1982-; John, Jory (Barnett, Mac <<The>> Terrible Two, 2016)
"Friends and pranking partners Miles and Niles face a tough challenge when their favorite goat and nemesis, Principal Barkin, is replaced by his stern, no-nonsense father, Principal Barkin Senior, who turns the school into boot camp"...